IMPLEMENTATION OF SEX EDUCATION IN CHILDREN IN ELEMENTARY SCHOOL 108 PALEMBANG - Siti Chodijah; Dianita Ekawati; Chairil Zaman (Majalah Kedokteran Sriwijaya, 2022)
The implementation of sex education to children is an application what children aged 8-10 years get about things related to sex education in the form of children tau and maintaining the cleanliness of their reproductive organs, children know what forms of sexual abuse are, children are able to protect themselves from sexual harassment.  The purpose of this study was to analyze the implementation of sex education in children at elementary school 108 Palembang. The population in this study were all 6th grade students aged 10-13 years, sample taken in this study 96 respondents using a total sampling technique. The chi square test results show that there is an association between the implementation of sex education in children with knowledge (P = 0.001, OR = 4.8, 95% CI = 1.9-12), role of parents (P = 0.000, OR = 6.95 CI = 2.6-13.6), role of homeroom teacher (P = 0,000, OR = 8.03, 95% CI = 3.05-21.1), role of friends (P = 0.010, OR = 3.8, 95% CI = 1.4-10), social media (P = 0.003, OR = 4.2, 95% CI = 1.6-10.4), facilities (P = 0.004, OR = 4.2, 95% CI = 1.6-11), religious norms (P = 0.036, OR = 2.7, 95% CI = 1.1-6.6). With the most dominant variable with the implementation of sex education in children is the role of the homeroom teacher (OR=8.519, 95% CI= 2.58-28.09). It is recommended that through this research, especially the parents to maintain the provision of good sex education to their students and start giving them to grade 5 children according to curriculum 13, and it is even better to provide sex education as early as possible to all students using appropriate language according to age.